Age‐ and sex‐related differences in diastolic function and cardiac dimensions in a hypertensive population. (14th July 2016) - Hoshida, Shiro; Shinoda, Yukinori; Ikeoka, Kuniyasu; Fukuoka, Hidetada; Inui, Hirooki; Watanabe, Tetsuya
Abstract: Aims: The prevalence of left ventricular diastolic dysfunction increases with age, particularly in hypertensive women. We aimed to determine the age‐ and sex‐related differences in diastolic function, and its relation to alterations of cardiac dimensions in a hypertensive population. Methods and results: We enrolled 479 hypertensive patients with a left ventricular ejection fraction (LVEF) ≥50% (men/women, 267/212) and their echocardiographic parameters regarding LV performance and vascular function were measured. Left atrial volume index (LAVI) and operant diastolic elastance (EdI: E/e′/stroke volume index), but not LV mass index (LVMI), correlated weakly with age in both sexes. The arterial elastance index (EaI) and EdI did not differ significantly between sexes in any of the three age groups (A, <65 years; B, ≥65 years but <75 years; C, age ≥75 years). The EdI indexed to EaI, EdI/EaI = E/e′/(0.9 × systolic blood pressure), was significantly more impaired in women than in men only in group C. There were significant differences in LAVI, LVMI, and EdI/EaI between groups B and C only in women. Conclusions: Impairment of diastolic function relative to arterial elasticity, EdI/EaI, occurred in elderly hypertensive women and was coincident with the alteration of cardiac dimensions. The coincidence with the changes in diastolic function and the alterations of cardiac dimensions occurred in a different time point between the sexes.